Classic Papers in Coronary Angioplasty - Handler, Clive; Cleman, Michael (Springer London : Imprint: Springer, 2006)
Every medical specialty has a core of classic papers that reflect both the historical development of the discipline and point the way to present and future developments. The Editors of Classic Papers in Coronary Angioplasty have assembled a distinguished team of international contributors, to identify, analyze and bring together in a single volume the most important articles from a broad range of publications that have become recognized as the defining articles in coronary angioplasty. This publication is a unique reference, for not only does it provide a single source for reviewing the most important papers in the discipline, it also provides a critical analysis of the strengths, weaknesses and the impact each paper has had on the development of coronary angioplasty. This book will be essential reading for cardiologists - in particular interventional cardiologists - radiologists, vascular surgeons and all involved in research and clinical practice in the field of coronary angioplasty.